Applying Mutation Testing in Prolog Programs - Toaldo, Juliano R.; Vergilio, Silvia R. (Anais do Workshop de Testes e Tolerância a Falhas (WTF); 2006: Anais do VII Workshop de Testes e Tolerância a FalhasDO - 10.5753/wtf.2006.23347, 2006)
Several testing criteria and tools have been proposed lately, with the goal of selecting and evaluating test data sets. However, most works focus only procedural and object-oriented programs and little has been said about logic programming languages, such as Prolog. Some works address the test of Prolog programs however, do not introduce a testing criterion and not offer coverage testing metrics. This work investigates the application of the Mutation Analysis criterion for testing Prolog programs. In experiments of literature, this criterion has been considered one of the most efficacious. A set of mutation operators for this language is proposed, based on common mistakes made by the programmers using this paradigm. A tool, named MutProlog, is described. This tool supports the proposed operators and eases the development of Prolog programs. Results from an experiment, using MutProlog, show the applicability of the proposed operators and allow comparison with structural criteria.